Field Activity for Cultural Anthropology - Haney, Wava (TRAILS: Teaching Resources and Innovations Library for Sociology, 2010)
In this course, I ask students to do three field activity projects that build on materials from the course, primarily readings and videos, and give them opportunities to use/develop skills that will be useful for their major project of the course, an ethnographic study of a cultural group with which they have limited familiarity or knowledge.